El mercado integrado latinoamericano (MILA) análisis comparativo de los mercados bursátiles de los países miembros - Moreno Pacheco, Stephanie Gabriela (2013)
The present graduation work makes reference to the process of integration known as Integrated Latin-American Market MILA, which is the integration of the stock market of Chile, Peru and Colombia and its respective value deposits. This investigation was made analyzing different concepts going from general to specific, this is because first of all the integration concepts and the stock market in separate were determined so that later on the background, the objectives, the development and the functioning of the Integrated Latin American Market could be analyzed and determined, as well as its benefits for the countries which pretend to form part of it, mainly Ecuador. With this investigation we pretend to demonstrate the importance of the stock market as a source to generate resources, as well as the importance to work cooperatively in order to generate integration processes in the current epoch. The benefits for Ecuador to form part of this market will be shown, by means of the comparative analysis of the stock-exchange of the markets of the three members of MILA, with the objective to stimulate the integration and to generate a greater culture towards the stock market in our country. The result of the investigation show that MILA has been a pioneer process of integration within the Latin American region, and although its short time functioning, it has generated good results locating itself within the three members, who being together created a solid block in the field of stock markets. With this work, through the obtained and analyzed information, we could determine that if Ecuador would like to enter this market, it would need to upgrade the stock market, making it a solid and reliable sector, it would also need to make changes in the normative and technological aspects so that they could make the way in order to form part of the MILA.